Penggambaran Perselingkuhan Pada Web Series Layangan Putus - Cahyana, Alia; Delliana, Anastasia Santi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
At the end of 2021, Layangan Putus web series, which is based on the true story of a woman, went viral and was liked by many people. Layangan Putus tells the story of a harmonious domestic life that begins to fall apart with the emergence of a third person, the relationship eventually becomes a toxic relationship. This study aims to determine of infidelity in the web series Layangan Putus by using a qualitative descriptive method based on the theory of Social Reality Construction by analyzing signs based on Peirce's semiotic analysis, namely sign, object and interpretant. The results of this study show a picture of Aris's infidelity such as betrayal, having intimate relationships, giving gifts, hugging and kissing other women besides his wife.